Имам Шамиль в романах Якуба Гордона "Kaukaz czyli Ostatnie dni Szamyla" и Мариам Ибрагимовой Имам Шамиль - Weretiuk, Oksana (Acta Neophilologica, 2021)
The Uprising of Imam Shamil is a tragic and vivid event in the history of the Caucasus, hence it is not surprising that writers of different peoples from different times turn to it. This article, with the employment of the comparative method, explores the literary image of Shamil created on the basis of historical events by the Polish writer Jakub Gordon in his historical novel Kaukaz czyli Ostatnie dni Szamyla. Powieść historyczna (1865) and by the Dagestan-Russian writer Mariam Ibragimova in her historical trilogy Imam Shamil (1991). The first novel was written by a contemporary of Polish military-political participants in the Caucasian War, who communicated with its witnesses, the second one – by a compatriot of Shamil, a modern Dagestan and Russian writer. The differences in time, place of writing, aesthetic backgrounds, and nationality of the authors of these two novels created in similar genres foresee some discrepancies in their artistic structure, ideological accents and focus on the displayed events.